2022
DOI: 10.2967/jnumed.122.263823
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of166Ho Radioembolization in Hepatocellular Carcinoma: The HEPAR Primary Study

Abstract: Safety and efficacy of 166 Ho-radioembolization was first determined in the HEPAR and HEPAR II studies, however excluding patients with hepatocellular carcinoma (HCC). The aim of this prospective clinical early phase II study was to establish the toxicity profile of 166 Ho-radioembolization in patients with measurable, liver-dominant HCC, BCLC stage B-C, Child-Pugh (CP) score ≤B7, ECOG 0-1 without curative treatment options.The primary endpoint was rate of unacceptable toxicity defined as grade 3 hyperbilirubi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The highest found healthy liver mean absorbed dose in that study was 55 Gy, and therefore, it has been recommended as the current healthy liver dose threshold. Similar safety data for patients with cirrhotic livers is expected in the near future from secondary analyses of the HEPAR Primary study [23,24]. An additional advantage of intraprocedural dosimetry is that the physician can assess not only the mean tumour dose in near real time, but also the coverage of tumours with microspheres through the heterogeneity of the dose distribution.…”
Section: Discussionmentioning
confidence: 64%
“…The highest found healthy liver mean absorbed dose in that study was 55 Gy, and therefore, it has been recommended as the current healthy liver dose threshold. Similar safety data for patients with cirrhotic livers is expected in the near future from secondary analyses of the HEPAR Primary study [23,24]. An additional advantage of intraprocedural dosimetry is that the physician can assess not only the mean tumour dose in near real time, but also the coverage of tumours with microspheres through the heterogeneity of the dose distribution.…”
Section: Discussionmentioning
confidence: 64%
“…[ 27 ]. To conclude, a phase II study assessing toxicity profile of 166 Ho in patients with hepatocellular carcinoma reported unacceptable toxicity in 10% of the treated patients, but no cases of radioembolization-induced liver disease [ 28 ]. Additionally, target liver lesions with complete or partial response were found to be 54% and 84% at three- and six-month follow-up, respectively.…”
Section: Clinical Studies On 166 Ho Radioembolizationmentioning
confidence: 99%
“…The median overall survival was 14.9 months (95 % CI 10.4 months-not reached), and median AFP levels declined 67 % (nadir). This study showed that 166 Ho-microsphere RE is a promising treatment option for HCC patients with limited complication risks [88].…”
Section: Neuroendocrine Neoplasiamentioning
confidence: 99%